2010
DOI: 10.1080/03235400802404791
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of phytotoxins fromPhomasp. FGCC#18 for the management ofParthenium hysterophorusL.

Abstract: Biological control is a relatively cheap and most feasible long-term approach for controlling deadly weeds. Parthenium hysterophorus L. is a pernicious weed, imposing deleterious economic effects on humans and livestock. Microbial products thus offer a non-chemical alternative for controlling a noxious, invasive and pernicious weed like Parthenium. Phoma is a well-known phytopathogen responsible for many diseases in plants and is known to produce an array of bioactive extracellular toxic compounds, i.e. agribi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Phytotoxicity damage had been studied by seedling and detached leaf bioassays. Results indicate, Tween 80 at 0.5% to be the best formulant, while the combination of Tween 80 and coconut oil at 0.5% was found to exhibit maximum damage to Parthenium seedlings and detached leaves (Quereshi et al, 2010). Thus in our present research work, results were in accordance to results obtained earlier wherein, Tween 80 has been reported to be most compatible formulant (Kalam et al, 2014).…”
Section: Results and Discussion:-supporting
confidence: 91%
See 1 more Smart Citation
“…Phytotoxicity damage had been studied by seedling and detached leaf bioassays. Results indicate, Tween 80 at 0.5% to be the best formulant, while the combination of Tween 80 and coconut oil at 0.5% was found to exhibit maximum damage to Parthenium seedlings and detached leaves (Quereshi et al, 2010). Thus in our present research work, results were in accordance to results obtained earlier wherein, Tween 80 has been reported to be most compatible formulant (Kalam et al, 2014).…”
Section: Results and Discussion:-supporting
confidence: 91%
“…Loss of turgidity, drying finally culminated into seedling collapse. Similar results have been reported by Quereshi et al, 2010). Detached leaf bioassay results depict toxicity which initiated with slight necrosis and at advanced stage after 48 hpt acute necrosis was observed with wilting of entire leaves leading to complete death of foliar tissue Formulation is a process of mixing the secondary metabolite or the microbe with some inert carriers to alter their physico-chemical characteristics to enhance the shelf life and field performance of resulting formulated product.…”
Section: Results and Discussion:-supporting
confidence: 83%
“…Such metabolites represent a large pool of compounds that can enhance crop growth and crop protection (Izurdiaga et al 2023). Quereshi and Pandey (2007) extracted the cell-free culture extract of Phoma sp. FGCCW#54 which exhibited excellent herbicidal properties against Parthenium hysterophorus.…”
Section: Cell-free Culture Filtrates With Herbicidal Valuesmentioning
confidence: 99%
“…suggested that pyrrolo [1,2a] pyrazine-1,4-dione, hexahydro-3-(2-methylpropyl) may be responsible for reduced plant height [50]. Quereshi et al [51] and Razaghi and Zafari [52] reported herbicidal activity on P. hysterophorus and Convolvulus arvensis (bind weed) from cell-free spent medium of Phoma sp. FGCC #18 and P. crystallifera.…”
Section: Phoma Sacc -A Genus With Bioherbicide Potentialmentioning
confidence: 99%